2020
DOI: 10.3389/fonc.2020.01565
|View full text |Cite
|
Sign up to set email alerts
|

NAP1L1: A Novel Human Colorectal Cancer Biomarker Derived From Animal Models of Apc Inactivation

Abstract: Results: Nap1l1 mRNA expression was increased in mouse small intestine following Apc deletion in a Myc dependant manner and was also increased in human CRC samples. Immunohistochemical NAP1L1 expression was decreased in human CRC samples relative to matched adjacent normal colonic tissue. In a separate cohort of 75 CRC patients, we found a strong correlation between NAP1L1 nuclear expression and overall survival in those patients who had stage III and IV cancers. Conclusion: NAP1L1 expression is increased in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Finally, multivariable analysis demonstrated that increased NAP1L1 expression is an independent prognosis marker for the overall survival in breast cancer. These data are consistent with the reported data on colorectal cancer [11,13] , suggesting that NAP1L1 promotes the pathogenesis of breast cancer and might be a potential tumor promoter in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, multivariable analysis demonstrated that increased NAP1L1 expression is an independent prognosis marker for the overall survival in breast cancer. These data are consistent with the reported data on colorectal cancer [11,13] , suggesting that NAP1L1 promotes the pathogenesis of breast cancer and might be a potential tumor promoter in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al observed that PRDM8 suppresses the occurrence and development of hepatocellular carcinoma pathogenesis by targeting NAP1L1. Furthermore, elevated NAP1L1 expression was observed to promote carcinogenesis in colorectal cancer and pancreatic neuroendocrine neoplasm [10][11][12][13][14] . However, the role and molecular basis of NAP1L1 in breast cancer have never been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAP1L1 participates in the miR-532-5p-mediated suppression of renal cancer cell proliferation. In colorectal cancer and pancreatic neuroendocrine neoplasm, NAP1L1 was found to be a biomarker, involved in the pathogenesis of these two types of cancers (Schimmack et al, 2014;Zhai et al, 2018;Queiroz et al, 2020). In HCC, NAP1L1 acts as a tumor promoter and is repressed by PRDM8 and let-7c-5p.…”
Section: Discussionmentioning
confidence: 99%
“…NAP1L1 belongs to the human counterpart of the yeast NAP-I protein, a histone-binding factor involved in the cumulative nucleosome formation. NAP1L1 has been shown as a potential tumor promoter and participates in the pathogenesis of several tumors including colorectal cancer, renal cancer, and pancreatic neuroendocrine neoplasm (Schimmack et al, 2014;Zhai et al, 2018;Queiroz et al, 2020). Recent studies on HCC showed that PRDM8 suppresses the occurrence of tumor via interacting with NAP1L1 (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%